Testing Leverage and Spillover Effects in Precious Metal ETFs - Chen, Jo-Hui; Trang Do, Thi Van (Scientific Research, 2018)
This research employed the Generalized Autoregressive Conditional Heteroskedasticity-in-Mean-Autoregressive Moving Average (GARCH-M-ARMA) and the Exponentially Generalized Autoregressive Conditional Heteroskedasticity-in-Mean-Autoregressive Moving Average (EGARCH-M-ARMA) models to investigate the spillover and leverage effects in the returns and volatilities of precious metal (base metal) ETFs. Significant positive relationships were found between precious metal (base metal) ETFs and precious metal (base metal) price indices. Further, the positive relationship between risk and return was illustrated in daily precious metal (base metal) ETFs.
Keywords: Precious Metal ETFs; Spillover Effect; Leverage Effect